2016
DOI: 10.1175/waf-d-16-0016.1
|View full text |Cite
|
Sign up to set email alerts
|

A Statistical Analysis of Steady Eyewall Sizes Associated with Rapidly Intensifying Hurricanes

Abstract: It is well known that hurricane intensification is often accompanied by continuous contraction of the radius of maximum wind (RMW) and eyewall size. However, a few recent studies have shown rapid and then slow contraction of the RMW/eyewall size prior to the onset and during the early stages of rapid intensification (RI) of hurricanes, respectively, but a steady state in the RMW (S-RMW) and eyewall size during the later stages of RI. In this study, a statistical analysis of S-RMWs associated with rapidly inten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
19
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 33 publications
3
19
0
Order By: Relevance
“…The rapid slow-down of RMW contraction and the subsequent S-RMW phenomenon are also apparent during the RI of intense TCs, for example, in the simulations of Hurricane Wilma (2005) by Chen et al (2011, hereafter C11), and Typhoon Megi (2010) by Wang and Wang (2014). More recently, Qin et al (2016) carried out a statistical analysis of the S-RMW phenomenon associated with rapidly intensifying hurricanes using 25-year Extended Best Track datasets, in order to see to what extent the S-RMW phenomenon, revealed mostly by TC models, occurs in real storms. They found that about 59% of the RI events at 24 h intervals associated with 55 rapidly intensifying hurricanes exhibited the S-RMW phenomenon, and that the S-RMW tends to occur more commonly in more intense hurricanes (i.e.…”
Section: Introductionmentioning
confidence: 94%
See 2 more Smart Citations
“…The rapid slow-down of RMW contraction and the subsequent S-RMW phenomenon are also apparent during the RI of intense TCs, for example, in the simulations of Hurricane Wilma (2005) by Chen et al (2011, hereafter C11), and Typhoon Megi (2010) by Wang and Wang (2014). More recently, Qin et al (2016) carried out a statistical analysis of the S-RMW phenomenon associated with rapidly intensifying hurricanes using 25-year Extended Best Track datasets, in order to see to what extent the S-RMW phenomenon, revealed mostly by TC models, occurs in real storms. They found that about 59% of the RI events at 24 h intervals associated with 55 rapidly intensifying hurricanes exhibited the S-RMW phenomenon, and that the S-RMW tends to occur more commonly in more intense hurricanes (i.e.…”
Section: Introductionmentioning
confidence: 94%
“…This result is consistent with the statistical analysis of Qin et al . (), who showed that RI processes are not always accompanied by contracting RMW, and that the S‐RMW is found more frequently in intense storms and in storms with small RMW.…”
Section: Spatio‐temporal Vortex Structures During Rimentioning
confidence: 99%
See 1 more Smart Citation
“…However, the result here is consistent with recent findings by Qin et al . [], who reported that the RI phase of TCs often occurred with constant RMWs after the rapid contraction. Since our main interest in this study was to evaluate the contribution of the near‐surface high energy air in the eye region to the intensification rate of the simulated TC, we focused on the RI phase and artificially modified the exchange coefficient for surface entropy flux calculation in the eye region after the first 36 h spinup period.…”
Section: Intensity Evolution Of the Simulated Stormsmentioning
confidence: 99%
“…Updrafts and downdrafts are highly concentrated within the eyewall, which is a ring surrounding the TC eye that comprises towering convective systems responsible for the most severe weather including the strongest winds (Aberson et al, ; Foerster et al, ). The intensification/weakening of a TC is usually accompanied by the variation of eyewall structure (Qin et al, ; Sitkowski et al, ). For example, the eyewall is established with a cycle of TC intensification and is broken down with a cycle of weakening (Wang, ).…”
Section: Introductionmentioning
confidence: 99%